The axiom about the market (cadastral) cost of the reproducible factors of a single propert - A. D. Vlasov (Статистика и экономика)
The purpose of the study. To prove the methodological error of the calculation of the market (cadastral) value of capital construction objects, as a result of a violation of the Federal law of the Russian Federation of 29.07.1998 No. 135-FZ “On valuation activities in the Russian Federation”, article 3, in determining the market value of the property. To show that the theory and practice of measuring the value of real estate is necessary to delimit the elements of the market value formation of reproducible and not reproducible factors single property. Materials and methods. The objectives of the article are: the rules of law in assessment activities; the results of the cadastral valuation of real estate in settlements of Russia; comparative analysis of the factors determining the market (cadastral) value of real estate. Results. Formulated the axiom about the market (cadastral) cost of the reproducible factors of a single property. It is shown that in the theory and practice of measurement in market (cadastral) value of real estate of Russia violated article 3 of the law 135-FZ of 29.07.1998. As a consequence, the market (cadastral) cost of the capital construction objects 2-5 times overestimated, and the market (cadastral) value of land in the 2-15 times underestimated. This is the basis of corruption, challenging the results of cadastral assessment of problems of formation of budgets of all levels, reduction in the rate of economic development of Russia. According to our results of the cadastral assessment of land plots of various categories of land in the regions of Russia there is a technology of determining the economic norms of rational use of real estate. Conclusion. Regardless of technology assessment of the property market value of reproducible improvements of the land may not exceed their replacement cost.